THE ROLES OF THE MAYOR OF TASIKMALAYA’S POLITICAL LEADERSHIP IN REDUCING POVERTY IN THE YEAR 2008-2013 - Tegar Ubaidillah Aldiansyah (IPem 15 UMY 472, 2015)
*472 This research tried to find the role of political leadership Mayor of Tasikmalaya in reducing poverty. The analysis of this research is more focus on making policy to reduce poverty and role of Mayor of Tasikmalaya. This research was a descriptive qualitative research. The technique to collect the data is by interview and documentation. The respondent of this research is Mayor of Tasikmalaya and some poor people. Data statistic for population of poor people it’s from Central Bureau Statistic (BPS). The percentage of poverty in the city of Tasikmalaya since 2008 is 26%, but the percentage decreases from year to year up to 2% per year, compared to other cities in West Java only decreases about 1%. Tasikmalaya is the fastest on reduction of poverty. On 2013 the percentage is reaching 17.19%. The result from 2014 until now the percentage of poverty is still waiting for the result from TNP2K and BPS. Keywords: Role of Mayor, Tasikmalaya, Reducing Poverty